A switched system approach to dynamic race modelling. (August 2016) - Blanchini, Franco; Casagrande, Daniele; Giordano, Giulia; Viaro, Umberto
Abstract: The paper presents and analyses some nonlinear continuous-time dynamic models of social systems whose members, groups or individuals, may change partners and/or opponents at any time, according to a greedy criterion. The main structural properties of these models, which belong to the class of positive switching systems, are investigated with particular regard to the existence of solutions, their positivity, boundedness and asymptotic behaviour. Simulations show how the cooperative or hostile attitudes of the participants affect their yield.